Natural pharmaceuticals and green microbial technology : health promotion and disease prevention - Mahapatra, Debarshi Kar; Shinde, Ravindra S., 1979-; Andhare, Aishwarya A.; Haghi, A. K. (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL, USA ; Abingdon, Oxon, UK : CRC Press, 2021)
"This volume presents some of the latest research and applications in using natural substances and processes for pharmaceutical products. It presents an in-depth examination of the chemical and biological properties of selected natural products that are either currently used or have the potential for useful applications in the chemical and pharmaceutical industries. It covers emerging technologies and case studies and is a source of up-to-date information on natural products and microbial technology. It provides an applied overview of the field, from traditional medicinal targets to cutting-edge molecular techniques. Natural products have always been of key importance to drug discovery, but as modern techniques and technologies have allowed researchers to identify, isolate, extract, and synthesize their active compounds in new ways, they are once again coming to the forefront of drug discovery. Topics include the safe use of use of petrochemical for various chemical and organic processes, the antibiotic and bio-herbicidal potential of extracts of Abutilon indicum and Prosopis juliflora, the health benefits of eugenol, stem cells and their connection with cancer, and more. Scientists, industry professionals, and graduate students will gain a unique insight into green microbial technology and natural pharmaceuticals today along with their practical implementation for health promotion and disease prevention."--
Green Solvents for Pharmaceuticals / G.S. Talele and H.V. Shahare -- Abutilon indicum and Prosopis juliflora as a Source of Antibiotic and Herbicidal Agents / Aishwarya A. Andhare and Ravindra S. Shinde -- Pharmacological Perspectives of Eugenol in Modern Context / Amena Ali and Abuzer Ali -- Predictive In Silico Global Metabolism Analysis : Disease Mechanism / Francisco Torrens and Gloria Castellano -- Intracellular Proteolysis and Neoplasia : Ubiquitin-Proteasome System, Cell Cycle, and Cancer / Francisco Torrens and Gloria Castellano -- Vitamin-D, Analogues, Drugs, and Their Relevance to Cancer Inhibition / Francisco Torrens and Gloria Castellano -- Stem Cells and Their Connection with Cancer : Prostate Disease / Francisco Torrens and Gloria Castellano -- MEK/ERK Pathway Overactivation in Liver Tumours : TGF-[Beta] Death / Francisco Torrens and Gloria Castellano -- Chalcone Scaffold Bearing Natural Anti-Gout Agents / Debarshi Kar Mahapatra, Vivek Asati, and Sanjay Kumar Bharti -- Double-Pole Electrode in New Devices and Processes for Direct Electrochemical Oxidation of Blood Inside the Blood Vessel / V. A. Rudenok -- Advanced Development in the Synthesis of Biologicaly Active Heterocyclic 1, 2, 3, 4 Tetrahydropyrimidine-2-ones / Kalpana N. Handore, Vasant V. Chabukswar, and S. B. Sharma.
OCLC-licensed vendor bibliographic record.
Keywords: Drug development; Natural products; Pharmaceutical microbiology; Pharmaceutical chemistry; Health promotion; Medicine, Preventive; MEDICAL / Pharmacology; SCIENCE / General; SCIENCE / Life Sciences / Biochemistry